Programmeringsundervisning og Systembeskrive - Mathiassen, Lars (DAIMI Report Series, 1979)
Different requirements are imposed upon the planning and teaching of a programming course. These requirements are primarily derived from the connection between production, qualification and education. Secondly, they are derived from the educational context of the programming course and from the knowledge and methods that have been developed in different areas of computer science. In the paper these requirements are discussed, and it is argued that they can be met in the planning and teaching of a programming course, when using system description as a starting point. Finally it is shown by an example how such a course can be arranged.